PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN EDUCAPLAY TERHADAP HASILO BELAJAR MATEMATIKA PESERTA DIDIK KELAS IV SDI AL-IKHLAS KECAMATAN KARANGREJO KABUPATEN TULUNGAGUNG - Hidayatus Shopiana, St Rahma; Yasip, Yasip (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study looks at how using Educaplay, an online learning tool, can improve math scores for fourth graders at Al-Ikhlas Islamic Primary School in Karangrejo District, Tulungagung. The problem is that teachers still use blackboards and books, which don't really get students excited about learning and can make it harder for them to understand the material. Educaplay, being an interactive online platform, is thought to be a good way to make learning more engaging and keep students focused. The study used a quasi-experimental method with two groups that aren't exactly the same. The process started with a test before the learning happened (pretest), then the experimental group used Educaplay for their lessons, and both groups took another test after (posttest). The results showed that using Educaplay actually helped improve math scores, as shown by the independent t-test with a significance level of 0.023 (p < 0.05). So, Educaplay works well to help students understand math better.